The role of mesenchymal stem cell-derived exosome in epigenetic modifications in inflammatory diseases - Zhao, Zihan; Zhang, Li; Ocansey, Dickson Kofi Wiredu; Wang, Bo; Mao, Fei (Frontiers in Immunology, 2023)
Epigenetic modification is a complex process of reversible and heritable alterations in gene function, and the combination of epigenetic and metabolic alterations is recognized as an important causative factor in diseases such as inflammatory bowel disease (IBD), osteoarthritis (OA), systemic lupus erythematosus (SLE), and even tumors. Mesenchymal stem cell (MSCs) and MSC-derived EXO (MSCs-EXO) are widely studied in the treatment of inflammatory diseases, where they appear to be promising therapeutic agents, partly through the potent regulation of epigenetic modifications such as DNA methylation, acetylation phosphorylation, and expression of regulatory non-coding RNAs, which affects the occurrence and development of inflammatory diseases. In this review, we summarize the current research on the role of MSC-EXO in inflammatory diseases through their modulation of epigenetic modifications and discuss its potential application in the treatment of inflammatory diseases.